Introduction to African Arabic: Approaches to Dialectology - (:unkn) unknown (My University, 2013)
Dialectology considers variation in language to be most commonly based on geographical distribution and its correlated phonological, grammaticaland lexical features. There are two approaches to dialectology: synchronicand diachronic ones. Synchronic dialectology studies the synchronic linguistic proximity of geographically contiguous language varieties. Diachronic, or historical, dialectology describes and explains the languageevolution and diffusion processes which lead to certain variations in form, meaning and structure by means of sociohistorical reconstructions. As these two approaches are interrelated, no clear-cut distinction can be made between them. Indeed, in variational linguistic research (viz. dialectology), any geographical diversity necessarily refers to temporal diversity (de Saussure 1973 [1916]; Lafkioui 2007). In addition to the horizontal (geographical, synchronic) and vertical (historical, diachronic) dimensions, linguistic variation also involves social diversity and individual diversity. The former – social diversity – includes parameters such as habitat (rural/urban), country of origin or country of immigration, gender, ethnicity, age, social class, educational level and educational type. The latter – individual diversity – partly overlaps with social variation, but also incorporates the ideological and psychohistorical aspects of the individual speakers (Lafkioui 2007, 2011a, Fc).In the case of African Arabic, it is historical rather than synchronic dialectology which is in need of additional and advanced study. A notable exception is the research conducted in creolistics, which is not only beneficial to dialectological but also to linguistic geographical studies (e.g. Kaye 1985; Miller 2002, 2004; Owens 2001; Versteegh 1993). The present volume aims at filling this gap, at least to a certain extent, by presenting thestate-of-the-art in research on African varieties of Arabic. It covers all the major areas of linguistic
Keywords: African Research